Picnic [videorecording (DVD)] - Logan, Joshua; Holden, William, 1918-1981; Novak, Kim; O'Connell, Arthur, 1908-1981; Strasberg, Susan; Robertson, Cliff, 1923-2011; Russell, Rosalind (Columbia classics., 2005)
The story covers one Labor Day week-end in a small Kansas town, and tells about the impact a virile drifter has on the lives of several women in town.